RETRACTED: Process of mechanical processing of cylindrical long parts and problems arising in the process - Fayzimatov Shuhrat; Khusanov Yunusali; Omonov Abdukaxxor; Matkarimov Behzod; Sadirov Shokhrukh; Yusufjonov Otabek; Turgunboev Temur (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001